Green Open Space Zoning in Supporting Sustainable Urban Environmental Management: A Case Study of the Distribution of Tribes and Indigenous Regions in Mountainous Papua (LAPAGO) - YM, Hardiyanti (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the zoning of green open spaces in the LAPAGO (Papua Mountains Customary Institution) region and reveal their existence and distribution in the context of sustainable urban environmental management. Furthermore, this study also wants to identify local wisdom applied by tribes in the Mountains region in managing green open spaces, so that cultural values can be integrated into regional planning and management. This research approach is a qualitative analysis based on observation, then the types of data and data sources collected in this study consist of primary data and secondary data from the Focus Group Discussion (FGD) activities of the Papua Mountains RTRW. The results obtained are that by identifying local wisdom applied by tribes in the Mountains region, this study shows how the practice of mutual cooperation and cultural values contribute to the effective management of green open spaces. The results of the study are expected to provide a basis for integrating cultural values in regional planning and management, supporting environmental sustainability, and preserving the cultural identity of indigenous communities.